2017
DOI: 10.1002/jsfa.8366
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hyperspectral indices, agronomic parameters and phenolic composition of Vitis vinifera cv Tempranillo grapes

Abstract: BACKGROUNDThe phenolic composition of grapes is key when making decisions about harvest date and ensuring the quality of grapes. The present study aimed to investigate the relationship between the detailed phenolic composition of grapes and the agronomic parameters and hyperspectral indices, with the latter being measured via field radiometry techniques.RESULTSGood correlations were found between phenolic composition (both anthocyanin and flavanol composition) and some hyperspectral indices related to vigor, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
4
10
0
Order By: Relevance
“…Specifically, the SVIs that were derived through proximal sensing had the highest correlations with table grape yield characteristics during the middle of veraison, while the satellite-derived SVIs presented their highest correlations during harvest. The latter is in accordance with Sun et al (2017), who found that the best crop stage for estimating wine grape yield from satellite-derived data is before harvest, while Garcia-Estevez et al (2017) found that the highest correlation of NDVI derived from proximal sensing with yield parameters of wine grapes was at veraison [57,58]. Thus, higher resolution data, such as proximal sensing data, can provide earlier crop yield and quality estimations compared to medium resolution remote sensing data.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the SVIs that were derived through proximal sensing had the highest correlations with table grape yield characteristics during the middle of veraison, while the satellite-derived SVIs presented their highest correlations during harvest. The latter is in accordance with Sun et al (2017), who found that the best crop stage for estimating wine grape yield from satellite-derived data is before harvest, while Garcia-Estevez et al (2017) found that the highest correlation of NDVI derived from proximal sensing with yield parameters of wine grapes was at veraison [57,58]. Thus, higher resolution data, such as proximal sensing data, can provide earlier crop yield and quality estimations compared to medium resolution remote sensing data.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the highest correlations were found at the same crop stage for each of the proximal and remote methods, during the middle of veraison (MV-2). This outcome agrees with the findings of Anastasiou et al [29] and Garcia-Estevez et al [92] which found also the highest correlation during the same growth stage (MV-2). Moreover, the highest correlation of S2-values in comparison to the CC-values, during all growth stages and especially in veraison, is probably related to the physiology of the vines.…”
Section: Vis-vbvs and Yield Correlationsupporting
confidence: 93%
“…Several relevant studies have shown a strong relationship between structural indices calculated from airborne multispectral datasets and fruit quality [17,102]. Compared to traditional structural indices, e.g., NDVI and SR, MTVI has been proven to be sensitive to variations in biophysical parameters by minimizing the asymptotic saturation effect caused by high density of vegetation [92,103]. Similarly, García-Estévez et al [103] found a strong performance of canopy reflectance-based GI for fruit quality estimation in their recent work, and this is confirmed in the current study.…”
Section: Contribution Of Vegetation Indices To Berry Yield and Qualitmentioning
confidence: 99%